Draft Second Five-Year Plan of Madhya Pradesh (1956-57 To 1960-61) In Two Volumes Vol. II-Appendices - Planning Commission (Planning Commission, 1956)
In order to meet the over-all increase in office-work due to implementation of the First Five- Year Plan and to cope with the responsibilities imposed by the Second Five-Year Plan, it is considered necessary strengthen the existing staff in the office of the Director of Agriculture, Madhya Pradesh. The scheme provided to suitable increase in staff.
Government of Madhya Pradesh, Planning and Development Department